Interview with Frank and Alice Halcrow - Halcrow, Frank; Halcrow, Alice; Capot, Dave; McLean, Dan (Canadian Plains Research Centre, 1972)
5 p. transcript of an interview with Frank and Alice Halcrow, conducted by Dave Capot and Dan McLean on November 21, 1972. Tape number IH-285, 285A, transcript disc 37. Frank Halcrow, aged 59, describes: taking of Treaty 8; establishment of reserves at Lesser Slave Lake; current problems due to small size of these reserves. Also tells story of a moose hunting expedition at time of great food shortage. Other no